2021
DOI: 10.12688/aasopenres.13107.2
|View full text |Cite
|
Sign up to set email alerts
|

Use of a mutation-specific genotyping method to assess for HIV-1 drug resistance in antiretroviral-naïve HIV-1 Subtype C-infected patients in Botswana

Abstract: Background: HIV-1 drug resistance poses a major threat to the success of antiretroviral therapy. The high costs of available HIV drug resistance assays prohibit their routine usage in resource-limited settings. Pan-degenerate amplification and adaptation (PANDAA), a focused genotyping approach based on quantitative PCR (qPCR), promises a fast and cost-effective way to detect HIV drug resistance mutations (HIVDRMs).  Given the high cost of current genotyping methods, we sought to use PANDAA for screening key HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The speed advantage is somewhat negated by the need to transfer samples to a centralized laboratory, but the simplified workflow is a distinct advantage. Versions of the PANDAA assay have been used in both treatment naïve [ 53 ] and treatment-experienced individuals [ 53 , 54 ], and a recent comparison in Zimbabwe [ 53 ] and Botswana [ 55 ] showed good agreement with Sanger sequencing results. PANDAA qDx HIVDR RTI is available for RUO applications.…”
Section: Methods Of Testing For Hiv Drug Resistancementioning
confidence: 99%
“…The speed advantage is somewhat negated by the need to transfer samples to a centralized laboratory, but the simplified workflow is a distinct advantage. Versions of the PANDAA assay have been used in both treatment naïve [ 53 ] and treatment-experienced individuals [ 53 , 54 ], and a recent comparison in Zimbabwe [ 53 ] and Botswana [ 55 ] showed good agreement with Sanger sequencing results. PANDAA qDx HIVDR RTI is available for RUO applications.…”
Section: Methods Of Testing For Hiv Drug Resistancementioning
confidence: 99%
“…(8) Zuo et al (9) reported that the M184V mutation causes resistance to lamivudine and that K103N is the most frequent mutation in nearly all NNRTI drugs. Maruapula et al (10) reported that there were one or more mutations in patients who failed first line therapy, with M184V and K103N being the most common. Drug resistance (DR) among HIV should receive more attention.…”
Section: Introductionmentioning
confidence: 99%